Efektifitas Sanksi Administratif dan Ketentuan Pidana pada Peraturan Daerah Kota Tanjungpinang Nomor 5 Tahun 2015 Tentang Ketertiban Umum - Sitorus, Rinto Gunawan (Universitas Internasional Batam, 2018)
To ensure the realization of peace and public order, the Tanjunginang City Government has established the Local Regulation Number 5 of 2015 concerning Public Order. In factual, in the enforcement of Regional Regulations and Regulations of the Head of Regional Units the Civil Service Police can carry out non-judicial operations. But in reality, the results of the study indicate that the application of administrative sanctions or criminal provisions against the Tanjungpinang Regional Regulation No. 5 of 2015 is not running optimally, this is due to several obstacles faced by the Civil Service Police Unit in the field, including its own Legal Factors , Law Enforcement Factors Are Alone, Facilities and Infrastructure Factors and Community Factors. In order for the enforcement of these regional regulations to work properly, the Tanjungpinang City Government should, in this case be carried out by the Civil Service Police Unit, be able to resolve these obstacles, one of which is by using the Legal Effectiveness theory proposed by Soerjono Soekanto in accordance with these 4 (four) factors.